Особливості формування структури середньозернистого твердого сплаву ВК20 за температури існування рідкої фази - Юрчук, М.О. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The paper describes the peculiarities of the formation of the medium-grained cobalt WC – 20Co cemented carbide at temperatures of 1300, 1350, 1360, 1400, 1450, 1470, 1500, 1550 and 1750 °C which permit formulating the principles of serial production of two-phase WC – Co cemented carbides having optimal carbon – free structure.